Effects of Knee Joint Exercises with Thai Hermit Exercise Program on Primary Knee Osteoarthritis Delay among Overweight Middle-aged Women - Khotwong, Varayuth; Singsalasang, Atthawit (Princess of Naradhiwas University Journal, 2023)
Middle aged overweight woman is regarded as a population at high risk of developing primary knee osteoarthritis. Age, gender, and overweight were significant indicators to develop the disease. A quasi-experimental design was used to investigate effects of a knee exercise program on prevention of primary osteoarthritis, which the exercise program was design based on Thai hermit postures and concepts of motivation in disease prevention of middle aged overweight women. The program received interrater opinion from experts at 0.91. Also, the program was evaluated by a questionnaire, received its reliability at 0.89. The samples were 74 middle aged overweight women living in Prakhonchai district, selected with simple random sampling. This quasi-experimental study divided participants into 2 groups; 37 persons for an experimental group and 37 persons for a control group. The participants did pre- and post-tests, and were followed up for 8 weeks during the program. Descriptive statistics and the t test were used to analyze data. The results of the experiment revealed that after implementing the knee training program with the experimental group, the group was measured in terms of the mean score of the effects of the program, which was greater than before the experiment and noticeably greater than the control group (p < 0.001). Thus, it is suggested to public health officers that the program be used among overweight middle-aged women to help delay primary knee osteoarthritis.